Antioxidant and antibacterial study of 10 flavonoids revealed rutin as a potential antibiofilm agent in Klebsiella pneumoniae strains isolated from hospitalized patients. (October 2021) - Wang, Zhibin; Ding, Zixuan; Li, Zhaoyinqian; Ding, Yinhuan; Jiang, Fan; Liu, Jinbo
Abstract: The emergence of multidrug resistance (MDR) and extensive drug resistance (XDR) in Klebsiella pneumoniae strains has posed great threats to conventional antibiotics. Previous studies have shown that plant-derived flavonoids have inhibitory functions against pathogens. However, in K . pneumoniae, the antibacterial activity of different flavonoids against growth and biofilm formation remains a mystery. The aim of the present study was to evaluate the antioxidant abilities of different flavonoids, to screen active ingredients and to identify their inhibitory effects on K . pneumoniae growth and biofilm formation. In total, 10 flavonoids representing 4 major categories were screened and used in this study. The antioxidant capacity of each flavonoid was evaluated through a DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay. Rutin showed the highest level of free radical scavenging capacity, followed by kaempferol, luteolin, quercetin, apigenin, hesperidin, sinensetin, naringenin, naringin and 3, 5, 6, 7, 8, 3′, 4′-heptamethoxyflavone. The inhibitory effects of rutin and naringin on bacterial growth were also compared. The lowest MICs of rutin were found against K. pneumoniae ATCC700603 (1024 μg/mL) and E. coli ATCC25922 (512 μg/mL). However, the MBICs were not found. Rutin showed strong inhibitory ability against both the growth curve and biofilm production. The expression profiles of 15 biofilm-related genes were analyzed in biofilm cells both with and without rutin treatment. The luxS gene and wabG gene were downregulated significantly by rutin treatment. Correlation analysis showed that mrkA gene expression was positively correlated with biofilm biomass accumulation. Our study indicated that biofilm production is correlated with the expression of several genes rather than one. MrkA gene expression was positively correlated with biofilm biomass accumulation. Our study screened rutin as a potential agent to inhibit K . pneumoniae biofilm formation. Highlights: Rutin showed strong inhibitory effect on planktonic cell growth in K. pneumoniae. Rutin significantly decreased biofilm production when the concentration was higher than 256 μg/mL. The expression of luxS gene and wabG gene was down-regulated after rutin treatment in strong biofilm producing K. pneumoniae. Biofilm production might be correlated with the expression of several genes rather than one. Rutin might be a potential agent to inhibit K. pneumoniae biofilm formation.